Analysis of Social Capital, Creativity, and Innovation on Business Sustainability - Rachmawati, Resti; Hamdani, Nizar Alam; Adiansyah, Adi (Jurnal Inovasi Bisnis dan Kewirausahaan, 2025)
This study is intended to test and analyze the influence of Social Capital, Creativity and Innovation on Business Sustainability. The population in this study are business actors on the scale of Micro, Small and Medium Enterprises in Garut Regency. This type of research is quantitative research with a descriptive approach. The sample used in this study was 400 respondents who were distributed to respondents and then processed using SPSS statistic 25 using simple random sampling techniques. The analytical tools used in this study were multiple linear regression, data quality test of determination coefficient and hypothesis test. The purpose of this study was to determine the influence of Social Capital, Creativity, and Innovation on the Sustainability of MSME Businesses in Garut Regency. The results of the study stated that the Social Capital Variable has a positive and significant influence of 52.7% on business sustainability. The Creativity Variable has a positive and significant influence of 50.5% on business sustainability. The Innovation Variable has a positive and significant influence of 32.4% on business sustainability. The variables of Social Capital, Creativity and Innovation have a positive and significant influence of 63.1% on business sustainability. While the remaining 36.9% is influenced by other variables not mentioned in this research model.